Separator for water electrolysis
By designing channels on the spacer to vent bubbles and optimizing the pore structure, the resistance and temperature problems caused by bubble accumulation in the zero-gap electrolytic cell are solved, the hydrogen formation efficiency is improved and mechanical and conductive properties are maintained.
Patent Information
- Application Number
- CN202380044122.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-30
- Filing Date
- 2023-05-23
- Publication Date
- 2025-01-10
AI Technical Summary
In a zero-gap electrolytic cell, bubble accumulation within the spacer results in high ion resistance, increased temperature and potential combustion risks, and increasing spacer to reduce bubble accumulation reduces ionic conductivity and increase complexity and cost.
A spacer for water electrolysis is designed, which has a channel on at least one side to discharge bubbles, the cross-section of the channel is large enough to discharge bubbles of 5 to 50 μm diameter, and by optimizing the pore structure and the thickness and pores of the pore layer Diameter to balance gas isolation and ionic conductivity.
It improves hydrogen formation efficiency, reduces the risk of ion resistance and temperature increase of the electrolytic cell, while maintaining mechanical strength and conductivity, and avoiding combustion of the isolation parts.
Smart Images

Figure CN119301307A_ABST
Abstract
Description
[0001] Technical Field of the Invention
[0002] The present invention relates to a separator for use in the electrolysis of water and to an electrolytic cell comprising such a separator.
[0003] Background of the Invention
[0004] Today, hydrogen is used in several industrial processes, such as its use as a raw material in the chemical industry and as a reducing agent in the metallurgical industry. Hydrogen is a basic building block for the manufacture of ammonia (and therefore fertilizers) and methanol (which is used in the manufacture of many polymers). Oil refineries, where hydrogen is used for the processing of intermediate oil products, are another area of use. However, the production of hydrogen from fossil fuels results in large amounts of CO2 emissions.
[0005] Hydrogen is also considered an important future energy carrier, which means that it can store and transport energy in a usable form. The energy is released by an exothermic combustion reaction with oxygen, thereby forming water. No greenhouse gases containing carbon are emitted during this combustion reaction.
[0006] To realize a low-carbon society, renewable energy utilizing natural energy such as sunlight and wind power is becoming increasingly important.
[0007] The production of electricity from wind and solar production systems depends largely on weather conditions and is therefore variable, which leads to an imbalance in electricity demand and supply. In order to store surplus electricity, so-called energy-to-gas technologies have attracted a lot of interest in recent years, in which electrical energy is used to produce gaseous fuels, such as hydrogen. As electricity production from renewable energy sources will increase, the need for storage and transportation of the produced energy will also increase.
[0008] Water electrolysis is an important manufacturing method in which renewable electricity can be converted into hydrogen. Hydrogen produced in this way is often referred to as green hydrogen, which emphasizes that no greenhouse gases are formed during its production. Ammonia and steel produced from or with green hydrogen are also called green ammonia and green steel.
[0009] In alkaline water electrolyzers, so-called separators or diaphragms are used to separate electrodes of different polarity to prevent short circuits between these electrodes and to prevent recombination of hydrogen (formed at the cathode) and oxygen (formed at the anode) by avoiding gas crossover. In addition, the separator should also be a highly ionic conductor for transporting hydroxyl ions from the cathode to the anode.
[0010] In so-called zero-gap electrolyzers, the electrodes are placed in direct contact with the separator, thereby reducing the distance between the two electrodes. Mesh-type or porous electrodes are used to enable the separator to be filled with electrolyte and to effectively remove the oxygen and hydrogen formed. It has been observed that such zero-gap electrolyzers can be operated at higher current densities, thereby improving the efficiency of the electrolysis.
[0011] However, in such zero-gap electrolytic cells, it has been observed that bubbles formed within the separator can migrate towards the upper region of the cell where they can accumulate. The accumulation of such bubbles can lead to a higher ionic resistance in this part of the cell. The temperature increase due to the inefficient cooling of the electrolyte in this region of the electrolytic cell can even lead to burning of the separator.
[0012] It has been observed that introducing a small distance between one side of the separator and at least one electrode results in less accumulation of gas bubbles within the separator.So-called spacers can be used to achieve the distance between the separator and the electrode.
[0013] However, the introduction of such spacers between the separator and one or more electrodes increases the complexity and cost of the zero-gap electrolytic cell and may further adversely affect its ionic conductivity, resulting in a less efficient electrolysis process.
[0014] Therefore, there is a need for a zero-gap electrolytic cell with improved hydrogen formation efficiency and a separator therefor. SUMMARY OF THE INVENTION
[0016] It is an object of the present invention to provide a separator for a more efficient zero-gap electrolytic cell.
[0017] This object is achieved with a spacer as defined in claim 1 .
[0018] Further objects of the present invention will become apparent from the following description.
[0019] BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 An embodiment of a separator according to the invention is schematically depicted.
[0021] Figure 2 Different channel patterns of separators according to the invention are schematically depicted.
[0022] Figure 3 An embodiment of a separator according to the invention is schematically depicted.
[0023] Figure 4 A further embodiment of a separator according to the invention is schematically depicted.
[0024] Figure 5 A top view of one embodiment of a zero-gap electrode-membrane assembly according to the present invention is schematically depicted.
[0025] Figure 6 One embodiment of a method for producing a separator according to the invention is schematically depicted. DETAILED DESCRIPTION OF THE INVENTION
[0027] Isolation
[0028] The separator (1) for water electrolysis according to the invention has on at least one side:
[0029] -Surface area S max ,
[0030] - Surface area S of the surface for contacting the electrode C ,and
[0031] - a channel (10) having a cross section Φ for venting gas bubbles C ,
[0032] Features:
[0033] -S C / S max ratio is 0.025 to 0.50, and
[0034] - The cross section Φ C Large enough to expel bubbles with a diameter of 5 to 50 μm.
[0035] The surface area S on one side of the spacer max corresponds to the surface area of one side of the separator before the channel (10) is incorporated into that side of the separator, such as Figure 1 as shown in .
[0036] The surface area S of one side of the spacer C is the total surface area of the electrodes (900, 900') that the separator can contact when placed in a zero-gap electrolytic cell, such as Figure 5 (Top view of a zero-gap membrane electrode assembly (MEA)).
[0037] Total surface area S (on one side of the spacer) C Calculated according to the following formula (I):
[0038]
[0039] The separator includes at least one channel on at least one side of the separator. Such a channel may also be referred to as a groove or a path. Such a channel is capable of discharging bubbles formed in such a channel upwardly toward the upper region of the electrolytic cell.
[0040] The channels of the separator described above must be distinguished from the pores of the separator described below. The pores in the separator according to the invention allow the electrolyte to pass through the separator. The diameter of these pores is optimized to prevent gases such as hydrogen or oxygen from passing through the separator. The channels of the separator according to the invention allow the formed gas bubbles to be discharged upwards (i.e. along the surface of the separator) towards the upper area of the electrolytic cell.
[0041] Gas bubbles formed near the electrodes due to electrolyte supersaturation can now be exhausted through the channels of the separator, rather than forming bubbles within the separator where such channels would not exist.
[0042] Channel Φ C The cross section of the gas bubble may be large enough to enable the formation and discharge of gas bubbles. The gas bubbles typically have a diameter of 5 to 50 μm.
[0043] S C / S max The ratio is 0.025 to 0.50, preferably 0.05 to 0.4, and more preferably 0.1 to 0.3. When the ratio is greater than 0.5, bubbles may be formed in the separator, resulting in less efficient electrolysis. When the ratio is less than 0.025, the physical strength of the separator may become too low.
[0044] The channels of the separator can have different shapes, sizes and orientations, such as Figure 1 and 2 as long as they are able to discharge the gas bubbles towards the upper region of the electrolytic cell.
[0045] The separator according to one embodiment of the invention comprises a channel on at least one side of the separator (see Figure 3 ).
[0046] According to another more preferred embodiment, the separator has channels ( Figure 4 ). The channels on one side of the separator may be different from the channels on the other side. However, preferred separators have the same channels on both sides.
[0047] A preferred separator for alkaline water electrolysis comprises a porous layer (200) provided on a porous support (100), such as Figure 3 As shown schematically in FIG.
[0048] A particularly preferred separator comprises a first porous layer (250) provided on one side of a porous support (100) and a second porous layer (250') provided on the other side of the porous support (see Figure 4 ). The first (250) and second (250') porous layers may be the same or different from each other.
[0049] The above-mentioned channels are preferably produced in these porous layers, as described below.
[0050] The porous layer preferably comprises a polymer and inorganic particles, both as described below.
[0051] The thickness (t2) of the separator is preferably 50 to 750 μm, more preferably 75 to 500 μm, most preferably 100 to 250 μm, and particularly preferably 125 to 200 μm. Increasing the thickness of the separator generally results in a higher physical strength of the separator. However, increasing the thickness of the separator may also result in a decrease in electrolysis efficiency due to an increase in ionic resistance.
[0052] The separator prevents the mixing of hydrogen and oxygen formed at the cathode and anode, respectively. Therefore, the separator preferably has a maximum pore diameter (PDmax) of 0.05 to 2 μm, more preferably 0.10 to 1 μm, and most preferably 0.15 to 0.5 μm, which is measured using the bubble point test method. The bubble point test method is described in American Society for Testing and Materials Standard (ASMT) Method F316. The technique is based on the displacement of the wetting liquid embedded in the separator by applying an inert pressurized gas.
[0053] The bubble point test method can be adapted to measure the maximum pore diameter (PDmax) on both sides of the separator by using a grid supporting one side of the separator during the measurement. Another measurement is then made using a grid supported to the other side of the separator. The PDmax measurement on both sides of the separator is preferably made on a separator having a porous layer on both sides of a porous support.
[0054] The PDmax measured on both sides of the separator may be substantially the same or different from each other.
[0055] A separator with similar PDmax on both sides has the advantage that a defect, such as a scratch, on one side of the separator does not immediately lead to a higher gas permeation through the separator, since small pores are still present on the other side of the separator.
[0056] The separator includes pores having a pore diameter that is small enough to prevent the recombination of hydrogen and oxygen by avoiding gas crossing in the longitudinal direction of the separator. On the other hand, in order to ensure efficient transport of hydroxyl ions from the cathode to the anode, the pore diameter may not be too small to ensure efficient penetration of the electrolyte into the separator.
[0057] A separator with different PDmax on both sides may have a better compromise between efficient gas isolation and ionic conductivity. Such a separator may have a PDmax(1) of the first porous layer that is preferably 0.05 μm to 0.3 μm, more preferably 0.08 μm to 0.25 μm, most preferably 0.1 μm to 0.2 μm, and a PDmax(2) of the second porous layer that is preferably 0.1 μm to 6.5 μm, more preferably 0.15 μm to 1.50 μm, most preferably 0.2 μm to 0.5 μm. The PDmax(2) / PDmax(1) ratio is preferably 1.1 to 20, more preferably 1.25 to 10, most preferably 2 to 7.5. A smaller PDmax(1) ensures effective isolation of hydrogen and oxygen, while PDmax(2) ensures good penetration of the electrolyte in the separator, resulting in sufficient ionic conductivity.
[0058] The spacer preferably has a 0.1 ohm.cm 2 or lower, more preferably 0.07ohm.cm 2 The ionic resistance in a 30 wt % KOH aqueous solution at 80° C. or lower. The ionic resistance can be obtained using the The measurements were made using a Multi 9310 IDS instrument equipped with a TetraCon 925 conductivity cell available from Xylem.
[0059] The porosity of the separator is preferably 30 to 70%, more preferably 40 to 60%. A separator having a porosity within the above range generally has excellent ion permeability and excellent gas barrier properties because the pores of the diaphragm are continuously filled with an electrolyte solution. A porosity of 80% or more will result in too low a mechanical strength of the separator and too high an electrolyte permeation, the latter leading to an increase in HTO (the weight % of hydrogen present in the oxygen formed at the anode).
[0060] The gas permeability of the membrane is preferably between 1 and 7 L / min.cm 2 Between, more preferably between 1.5 and 6.5 L / min.cm 2 Between 2 and 5.5 L / min.cm 2 between.
[0061] Porous carrier
[0062] A porous support may be used to reinforce the separator to ensure its mechanical strength.
[0063] The thickness (t1) of the porous support is preferably 350 μm or less, more preferably 200 μm or less, most preferably 100 μm or less, particularly preferably 75 μm or less.
[0064] It has been observed that as the thickness of the porous support decreases, the ionic conductivity through the reinforced separator increases.
[0065] However, in order to ensure sufficient mechanical properties of the reinforced separator, the thickness of the porous support is preferably 20 μm or more, more preferably 40 μm or more.
[0066] The porous support may be selected from porous fabrics and porous ceramic plates.
[0067] The porous carrier is preferably a nonwoven fabric, a woven fabric, a net or a felt, more preferably a nonwoven fabric or a woven fabric.
[0068] The porous support is preferably a porous fabric, more preferably a porous polymer fabric.
[0069] The porous polymer fabric can be woven or nonwoven. Woven fabrics generally have better dimensional stability and uniformity of open area and thickness. However, the manufacture of woven fabrics with a thickness of 100 μm or less is more complicated, which results in a more expensive fabric. The manufacture of nonwoven fabrics is less complicated, even for fabrics with a thickness of 100 μm or less. In addition, nonwoven fabrics can have a larger open area.
[0070] The open area of the porous support is preferably between 30 and 80%, more preferably between 40 and 70%, to ensure good penetration of the electrolyte into the support.
[0071] The fabric preferably has a fiber diameter of 20 μm to 200 μm, more preferably 40 μm to 150 μm, and most preferably 60 μm to 100 μm. A fabric having a smaller thickness preferably has a smaller fiber diameter. For example, a fabric having a thickness t1 of 150 μm or less preferably has a fiber diameter of 75 μm or less, more preferably 50 μm or less, and most preferably 35 μm or less.
[0072] To further reduce the thickness t1 of the fabric, the ratio of web thickness to fiber diameter is preferably less than 2.0, more preferably 1.7 or less, most preferably 1.4 or less. Thinner fabrics allow thinner separators to be prepared.
[0073] Suitable porous polymer fabrics are prepared from polypropylene (PP), polyethylene (PE), polysulfone (PSU), polyphenylene sulfide (PPS), polyamide / nylon (PA), polyethersulfone (PES), polyphenylsulfone (PPSU), polyethylene terephthalate (PET), polyether-etherketone (PEEK), sulfonated polyether-etherketone (s-PEEK), monochlorotrifluoroethylene (CTFE), copolymers of ethylene and tetrafluoroethylene (ETFE) or chlorotrifluoroethylene (ECTFE), polyimide, polyetherimide and meta-aramid.
[0074] Preferred polymer fabrics are made from polypropylene (PP), polyetheretherketone (PEEK) or polyphenylene sulfide (PPS), most preferably made from polyetheretherketone (PEEK) or polyphenylene sulfide (PPS).
[0075] The porous supports based on PPS or PEEK have high resistance to high temperature, high concentration alkaline solutions and high chemical stability against active oxygen released from the anode during the water electrolysis process. In addition, PPS and PEEK can be easily processed into various forms, such as woven fabrics or nonwoven fabrics.
[0076] The density of the porous support is preferably between 0.1 and 0.7 g / cm 3 between.
[0077] The porous support is preferably a continuous web to enable the manufacturing methods as disclosed in EP-A 1 776 490 and WO 2009 / 147084.
[0078] The width of the web is preferably between 30 and 300 cm, more preferably between 40 and 200 cm.
[0079] polymer
[0080] The porous layer comprises a polymer.
[0081] As described below, the polymer forms a three-dimensional porous network as a result of a phase inversion step in the preparation of the separator.
[0082] The polymer resin may be selected from fluorine resins such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE), olefin resins such as polypropylene (PP), and aromatic hydrocarbon resins such as polyethylene terephthalate (PET) and polystyrene (PS). The polymer resin may be used alone, or two or more polymer resins may be used in combination.
[0083] PVDF and vinylidene fluoride (VDF) copolymers are preferred for their anti-oxidation / reduction and film-forming properties. Among these, terpolymers of VDF, hexafluoropropylene (HFP) and chlorotrifluoroethylene (CTFE) are preferred for their excellent swelling properties, heat resistance and adhesion to electrodes.
[0084] Another preferred polymer is an aromatic hydrocarbon polymer because of their excellent heat resistance and alkali resistance. Examples of aromatic hydrocarbon polymers include polyethylene terephthalate, polybutylene terephthalate, polybutylene naphthalate, polystyrene, polysulfone, polyethersulfone, polyphenylene sulfide, polyphenylene sulfone, polyacrylate, polyetherimide, polyimide and polyamide-imide.
[0085] Particularly preferred polymer resins are selected from the group consisting of polysulfone, polyethersulfone, polyphenylene sulfide, polyetheretherketone and polyphenylene sulfone, with polysulfone being most preferred.
[0086] The molecular weight (Mw) of the polymer is preferably between 10000 and 500000, more preferably between 25000 and 250000. When the Mw is too low, the physical strength of the porous layer may become insufficient. When the Mw is too high, the viscosity of the coating solution (see below) may become too high.
[0087] Examples of polysulfones, polyethersulfones, and combinations thereof are disclosed in EP-A 3085815, paragraphs
[0021] to
[0032] .
[0088] The amount of polymer is preferably from 5 to 40% by weight, more preferably from 10 to 30% by weight, most preferably from 15 to 25% by weight, all relative to the total dry weight of the porous layer.
[0089] Inorganic particles
[0090] The porous layer preferably contains inorganic particles. The inorganic particles make the porous layer hydrophilic. The hydrophilic nature of the porous layer prevents the adhesion of hydrogen and oxygen bubbles to the surface of the separator. The adhesion of such bubbles will reduce the electrolysis efficiency.
[0091] Preferred inorganic particles are selected from metal oxides and metal hydroxides.
[0092] Preferred metal oxides are selected from zirconium oxide, titanium oxide, bismuth oxide, cerium oxide and magnesium oxide.
[0093] Preferred metal hydroxides are selected from zirconium hydroxide, titanium hydroxide, bismuth hydroxide, cerium hydroxide and magnesium hydroxide. Particularly preferred magnesium hydroxide is disclosed in EP-A 3660188, paragraphs
[0040] to
[0063] .
[0094] Other preferred inorganic particles are sulfates of calcium, barium, lead or strontium, with barium sulfate particles being more preferred.
[0095] Still other inorganic particles that may be used are nitrides and carbides of elements of Group IV of the periodic table.
[0096] Combinations of one or more different inorganic particles may be used.
[0097] Inorganic particles can be natural or synthetic substances.
[0098] The surface of the inorganic particles may be untreated, or may be surface-treated with, for example, a silane coupling agent, stearic acid, oleic acid, or a phosphoric acid ester.
[0099] The shape of the inorganic particle is not particularly limited as long as it is in the form of particles, and may be any of an irregular shape, a spherical shape such as a true sphere and an ellipsoidal shape, a plate shape such as a thin plate shape and a hexagonal plate shape, and a fiber shape.
[0100] The inorganic particles preferably have a D of 0.05 to 2.0 μm, more preferably 0.1 to 1.5 μm, most preferably 0.15 to 1.00 μm, and particularly preferably 0.2 to 0.75 μm. 50 Particle size. 50 The particle size is preferably 0.7 μm or less, more preferably 0.55 μm or less, most preferably 0.40 μm or less.
[0101] D 50 Particle size is also called median diameter or the middle value of the particle size distribution. It is the particle diameter value at 50% of the cumulative distribution. For example, if D 50 =1.0 μm, then 50% of the particles are larger than 1.0 μm and 50% are smaller than 1.0 μm.
[0102] Preferably laser diffraction is used, for example using a Mastersizer from Malvern Panalytical to measure D 50 granularity.
[0103] The amount of inorganic particles is preferably 30 to 95 wt %, more preferably 50 to 92 wt %, most preferably 60 to 90 wt %, all relative to the total dry weight of the porous layer. The amount of inorganic particles is preferably at least 65 wt %, more preferably at least 75 wt %, all relative to the total dry weight of the porous layer.
[0104] The weight ratio of the hydrophilic particles to the polymer resin is preferably 60 / 40 or more, more preferably 70 / 30 or more, and most preferably 75 / 25 or more.
[0105] Preparation of spacers
[0106] The preparation of the separator according to the present invention comprises the following steps, wherein a channel for discharging air bubbles is provided on at least one side of the separator.
[0107] For the porous separator for alkaline water electrolysis, the preferred preparation method comprises the following steps:
[0108] - applying a coating solution as described below onto one side of the porous support (100);
[0109] - subjecting the applied coating solution to phase inversion, thereby forming a separator (1) comprising a porous layer (200) on the support; and
[0110] - During the phase inversion step, channels (60) are provided into the porous layer (200).
[0111] The channels are preferably provided in the early stages of the phase inversion step.
[0112] The coating solution can be applied to both sides of the porous support (100) to obtain a separator (1) comprising first and second porous layers (250, 250') on one side and the other side of the porous support, respectively. In this case, the channels are provided in at least one porous layer, preferably in both porous layers.
[0113] The step of providing channels into the porous layer of the separator is preferably incorporated into the methods of making reinforced separators disclosed for symmetrical separators in EP-A 1776490 and WO2009 / 147084 and for asymmetrical separators in EP-A 3652362. These methods produce web-reinforced separators in which the web (i.e. the porous support) is well embedded in the separator without the web being present at the surface of the separator.
[0114] Other methods of manufacture which may be used are disclosed in EP-A 3272908, EP-A 3660188 and EP-A 3312306.
[0115] Coating solution
[0116] The coating solution preferably contains the polymer described above, the inorganic particles described above, and a solvent.
[0117] The solvent of the coating solution is preferably an organic solvent in which the polymer can be dissolved. In addition, the organic solvent is preferably miscible in water.
[0118] The solvent is preferably selected from N-methyl-pyrrolidone (NMP); N-ethyl-pyrrolidone (NEP); N-butyl-pyrrolidone (NBP); N,N-dimethyl-formamide (DMF); formamide; dimethyl sulfoxide (DMSO); N,N-dimethyl-acetamide (DMAC); acetonitrile; and mixtures thereof.
[0119] For health and safety reasons, a highly preferred solvent is N-butyl-pyrrolidone (NBP).
[0120] The coating solution may further comprise other ingredients in order to optimize the properties of the obtained porous polymer layer.
[0121] The coating solution preferably contains additives to optimize the pore size at the surface and within the porous layer.Such additives may be organic or inorganic compounds, or a combination thereof.
[0122] Organic compounds that can affect the formation of pores in the porous layer include polyethylene glycol, polyethylene oxide, polypropylene glycol, ethylene glycol, tripropylene glycol, glycerol, polyols, dibutyl phthalate (DBP), diethyl phthalate (DEP), heinicosyl phthalate (DUP), isononanoic acid or neodecanoic acid, polyvinyl pyrrolidone, polyvinyl alcohol, polyvinyl acetate, polyethylene imine, polyacrylic acid, methyl cellulose and dextran.
[0123] Preferred organic compounds which can influence the formation of pores in the porous layer are selected from polyethylene glycol, polyethylene oxide and polyvinyl pyrrolidone.
[0124] Preferred polyethylene glycols have a molecular weight of 10,000 to 50,000, preferred polyethylene oxides have a molecular weight of 50,000 to 300,000, and preferred polyvinyl pyrrolidone has a molecular weight of 30,000 to 1,000,000.
[0125] A particularly preferred organic compound which can influence the formation of pores in the porous layer is glycerol.
[0126] The amount of the compound capable of influencing pore formation is preferably from 0.1 to 15% by weight, more preferably from 0.25 to 10% by weight, most preferably from 0.5 to 2.5% by weight, all relative to the total weight of the coating solution.
[0127] Inorganic compounds that can affect pore formation include calcium chloride, magnesium chloride, lithium chloride, and barium sulfate.
[0128] Combinations of two or more additives that affect pore formation may be used.
[0129] The coating solutions provided on either side of the porous support may be the same or different.
[0130] Applying coating solution
[0131] The coating solution may be applied to the surface of a substrate, preferably a porous support, by any coating or casting technique.
[0132] The preferred coating technique is extrusion coating.
[0133] In a highly preferred embodiment, the coating solution is applied to at least one side of the porous support by a slot die coating technique.
[0134] The slot coating die is capable of maintaining the coating solution at a predetermined temperature, uniformly distributing the coating solution on the support, and regulating the coating thickness of the applied coating solution.
[0135] In 100s -1The viscosity of the coating solution, measured at a shear rate of 1000 Å and a temperature of 20° C., is preferably at least 7.5 Pa.s, more preferably at least 15 Pa.s, most preferably at least 30 Pa.s.
[0136] The coating solution is preferably shear thinning. -1 The viscosity of the shear rate is related to the -1 The ratio of the shear rate to the viscosity is preferably at least 2, more preferably at least 2.5, most preferably at least 5.
[0137] In a preferred method of manufacture (see Figure 6 ), two slot coating dies (600 and 600') are located on either side of the porous support (100). The porous support is preferably a continuous web that is transported downwardly between the slot coating dies (600, 600').
[0138] After applying the one or more coating solutions to the porous support, the porous support immediately becomes impregnated with the one or more coating solutions.
[0139] Preferably, the porous support becomes completely impregnated with the applied coating solution or solutions.
[0140] Phase inversion step
[0141] After the coating solution is applied to the porous support, the applied coating solution is subjected to a phase inversion (also called phase separation). In the phase inversion step, the applied coating solution is converted into a porous layer.
[0142] Any phase inversion mechanism may be used to produce the porous layer from the applied coating solution.
[0143] The phase inversion step preferably comprises a so called liquid induced phase separation (LIPS) step, a vapour induced phase separation (VIPS) step or a combination of VIPS and LIPS steps. The phase inversion step preferably comprises both VIPS and LIPS steps.
[0144] Both LIPS and VIPS are non-solvent-induced phase inversion processes.
[0145] In the LIPS step, a porous support provided with a coating solution is contacted with a non-solvent that is miscible with the solvent of the coating solution.
[0146] Typically, this is done by immersing the porous support provided with the coating solution or solutions into a non-solvent bath (also referred to as a coagulation bath).
[0147] The non-solvent is preferably water; a mixture of water and an aprotic solvent; an aqueous solution of a water-soluble polymer such as PVP or PVA; or a mixture of water and an alcohol such as ethanol, propanol or isopropanol; the aprotic solvent is selected from N-methylpyrrolidone (NMP), dimethylformamide (DMF), dimethyl sulfoxide (DMSO) and dimethyl-acetamide (DMAC).
[0148] Most preferably, the non-solvent is water.
[0149] The temperature of the coagulation bath is preferably between 20 and 90° C., more preferably between 40 and 70° C. The residence time of the separator in the coagulation bath is preferably from 1 minute to 1 hour, more preferably from 5 to 30 minutes.
[0150] Transfer of solvent from the coated polymer layer to the non-solvent bath and transfer of non-solvent into the polymer layer results in phase inversion and formation of a three-dimensional porous polymer network. Impregnation of the applied coating solution into the porous support results in the resulting hydrophilic layer being fully adhered to the porous support.
[0151] In a preferred embodiment, the porous carrier (100) provided with the coating solution on one or both sides is transported downwardly toward the coagulation bath (800) in a substantially vertical position (see Figure 6 ).
[0152] In the VIPS step, the porous support coated with the coating solution is exposed to a non-solvent vapor, preferably humid air.
[0153] Preferably, the phase inversion step comprises both VIPS and LIPS steps. Preferably the VIPS step is performed before the LIPS step.
[0154] exist Figure 6 In a preferred embodiment schematically shown in , the VIPS step is performed in a region 400 between the slot coating die (600, 600') and the surface of the non-solvent in the coagulation bath (800), which region 400 can be isolated from the environment by, for example, an insulating metal plate (500, 500').
[0155] In the preferred case where the coagulation bath contains water, the VIPS area (400) is filled with humid air.
[0156] The extent and rate of water transfer in the VIPS step can be controlled by adjusting the air velocity, the relative humidity and temperature of the air, and the exposure time.
[0157] The exposure time can be adjusted by varying the distance d1 between the slot coating die (600, 600') and the surface of the non-solvent in the coagulation bath (800) and / or the speed (v) at which the elongated web (100) is transported from the slot coating die toward the coagulation bath.
[0158] The relative humidity in the VIPS zone (400) can be adjusted by the temperature of the coagulation bath and the isolation of the VIPS zone from the environment and from the coagulation bath.
[0159] The VIPS steps performed on one side of the separator and on the other side of the separator to produce the second porous polymer layer may be identical to each other, as disclosed in EP-A 3652362.
[0160] High RH and / or high air velocity in the VIPS region generally results in a larger maximum pore diameter.
[0161] After the phase inversion step, preferably after the LIPS step in a coagulation bath, a washing step may be performed.
[0162] After the phase inversion step or the optional washing step, a drying step may be carried out.
[0163] Provide access
[0164] The channels may be provided in the porous layer by any technique. However, the provision of the channels may not substantially alter the properties of the separator such as gas barrier, physical strength and electrical conductivity.
[0165] For example, the channels may be provided by engraving techniques such as laser engraving. For example, a CO2 laser may be used to engrave the channels into the insulation.
[0166] Preferred techniques that can be used to provide the channels are selected from knurling, embossing and rotogravure.
[0167] Knurling is a manufacturing process whereby a pattern of straight, angled or intersecting lines is rolled into a material.
[0168] Embossing is a stamping process used to produce a pattern into a material. A negative image of the pattern to be formed into the material is pressed into the material.
[0169] In rotogravure printing, a negative image of the pattern to be formed is engraved into a printing roller.The pattern in the porous layer is formed by pressing the porous layer against the printing roller.
[0170] In the case of a porous separator for alkaline water electrolysis, the provision of the channels may not substantially change the properties of the porous layer, such as its porosity or the diameter of the pores. Thus, preferably, the channels are provided during the phase inversion step, preferably during the LIPS step. It is particularly preferred to provide the channels in the early stages of the phase inversion step.
[0171] When channels are provided into the separator by some kind of impression technique at the end of the separator production process, separator properties such as porosity may become non-uniform.
[0172] For porous separators used in alkaline water electrolysis, preferably channels are provided during the phase inversion step, more preferably during the LIPS step.
[0173] Before providing channels into the porous layer, the porous layer needs sufficient strength. For this reason, LIPS is preferably ongoing when introducing channels into the porous layer. On the other hand, when LIPS is completed, providing channels may become more difficult.
[0174] In a preferred method of preparing a separator, the separator has channels provided on both sides of the separator, which is schematically shown in Figure 6 During the LIPS step, the channels are provided by rotogravure rolls 800 and 800'. To prepare a separator with channels on only one side, rotogravure roll 800 can be used to provide the channels, while roll 800' is then preferably replaced by a backing roll.
[0175] The distance d2 between the entry of the separator into the coagulation bath (start of the LIPS step) and the provision of the channel into the porous layer can be optimized to achieve an optimal channel. When the distance d2 increases (at a constant transport speed v of the separator), the LIPS process when providing the channel into the porous layer proceeds to a higher degree. When the LIPS process proceeds to a too high degree, the porous layer may become too hard to obtain an optimal channel. When the distance d2 is too short, the solidification of the porous layer may not be sufficient to obtain a channel.
[0176] The transmission speed v can also be optimized to obtain the best channel.
[0177] Package
[0178] It has been observed that the water content of the manufactured separator can affect its mechanical properties. Therefore, preferred packaging ensures that the water content remains substantially constant even when the packaged film is stored for several months at different temperatures and / or relative humidity.
[0179] Preferably, at least 25% by volume, more preferably at least 40% by volume, most preferably at least 50% by volume of the pores of the separator are filled with water. In a particularly preferred embodiment, at least 75% by volume of the pores are filled with water.
[0180] The volume % of pores filled with water (volume % P) is determined by the method described below.
[0181] Usually the separator is cut into sheets of different sizes, and then a certain amount of these sheets are packaged. Interleaves can be used to separate the sheets in the package.
[0182] The water vapour transmission rate (WVTR) of a packaging material gives an indication of the diffusion of water vapour into and out of the package.
[0183] The WVTR of the packaging for the separator according to the present invention is preferably less than 5 g / m 2 / 24 hours, more preferably less than 2.5g / m 2 / 24 hours, most preferably less than 1g / m 2 / 24 hours, particularly preferably less than 0.5 g / m 2 / 24 hours. However, the WVTR of the package can be less than 0.1g / m 2 / 24 hours or even less than 0.01g / m 2 / 24 hours.
[0184] Any packaging material having the above-mentioned WVTR values may be used.
[0185] Typical packaging materials include barrier laminates made from different foils / materials such as aluminum, polyethylene (PE), polyethylene terephthalate (PET), oriented polypropylene (OPP) or nonwovens. Such barrier laminates are usually provided on a core, such as paperboard.
[0186] A preferred barrier laminate is for example a PET / PE laminate, for example a PET / PE laminate of 12 μm (+ / -10%) PET foil and 75 μm (+ / -15%) PE foil. The barrier laminate is then preferably provided on a paperboard, for example a 76 mm thick paperboard.
[0187] Electrolytic Cell
[0188] The separator for alkaline water electrolysis according to the present invention can be used in an alkaline water electrolyzer.
[0189] An electrolytic cell generally consists of two electrodes, an anode and a cathode, separated by a separator. An electrolyte is present between the two electrodes.
[0190] When an electric current is supplied to the electrolytic cell, the hydroxyl ions of the electrolyte are oxidized to oxygen at the anode, and water is reduced to hydrogen at the cathode. The hydroxyl ions formed at the cathode migrate to the anode through the separator. The separator prevents mixing of the hydrogen and oxygen formed during electrolysis.
[0191] The electrolyte solution is typically an alkaline solution. A preferred electrolyte solution is an aqueous solution of an electrolyte selected from sodium hydroxide or potassium hydroxide. Potassium hydroxide electrolytes are typically preferred due to their higher specific conductivity. The concentration of the electrolyte in the electrolyte solution is preferably 20 to 40% by weight relative to the total weight of the electrolyte solution.
[0192] The temperature of the electrolyte is preferably 50 to 120° C., more preferably 75 to 100° C., most preferably 80 to 90° C. However, higher temperatures, such as at least 100° C., more preferably 125 to 165° C., may result in more efficient electrolysis.
[0193] The electrodes usually comprise a substrate provided with a so-called catalyst layer. The catalyst layer may be different for the anode forming oxygen and the cathode forming hydrogen.
[0194] Typical substrates are made of conductive materials selected from nickel, iron, mild steel, stainless steel, vanadium, molybdenum, copper, silver, manganese, platinum group elements, graphite and chromium. The substrate can be made of a conductive alloy of two or more metals or a mixture of two or more conductive materials. Preferred materials are nickel or nickel-based alloys. Nickel has good stability in strongly alkaline solutions, has good electrical conductivity and is relatively cheap.
[0195] The catalyst layer preferably comprises nickel, cobalt, iron and platinum group elements. The catalyst layer may comprise these elements as elemental metals, compounds (e.g. oxides), composite oxides or alloys made from a variety of metal elements, or mixtures thereof. Preferred catalyst layers comprise plated nickel, plated alloys of nickel and cobalt or nickel and iron, composite oxides comprising nickel and cobalt such as LaNiO3, LaCoO3 and NiCo2O4, compounds of platinum group elements such as iridium oxide, or carbon materials such as graphene.
[0196] A particularly preferred catalyst layer comprises Raney nickel. The Raney nickel structure is formed by selectively leaching aluminum or zinc from a Ni-Al or Ni-Zn alloy. The lattice spaces formed during leaching result in a large surface area and a high lattice defect density, which are active sites for electrocatalytic reactions to occur.
[0197] Preferred porous electrodes and methods for their production are disclosed, for example, in EP-A 3575442, paragraphs 23 to 84.
[0198] The pore size of the porous electrode can have an influence on the electrolysis efficiency. For example, in EP-A 3575442 it is disclosed that the preferred pore size of the porous electrode is 10 nm up to 200 nm.
[0199] The catalyst layer may also contain organic materials such as polymers to improve durability and adhesion to the substrate.
[0200] The separator according to the invention is preferably used in so-called zero-gap electrolyzers. In such zero-gap electrolyzers, the electrodes are placed in direct contact with the separator, thereby reducing the space between the two electrodes. Mesh-type or porous electrodes are used to enable the separator to be filled with electrolyte and to efficiently remove the oxygen and hydrogen formed. It has been observed that such zero-gap electrolyzers operate at higher current densities.
[0201] A typical alkaline water electrolyser comprises several electrolytic cells, also called a stack of electrolytic cells.
[0202] Regarding the battery configuration, two types of electrolyzers are commonly used.
[0203] A monopolar (or "can") electrolyzer consists of alternating positive and negative electrodes kept separate by separators. All of the positive electrodes are connected together in parallel, as are the negative electrodes, and the entire assembly is immersed in a single electrolyte bath (the "can") to form a unit cell. An equipment-scale electrolyzer is then built by electrically connecting these units in series. The total voltage applied to the entire electrolytic cell is the same as that applied to the individual unit cells.
[0204] In a bipolar electrolyzer, on the other hand, a metal sheet (or "bipolar body") electrically connects adjacent cells in series. The electrocatalyst for the negative electrode is coated on one face of the bipolar body, and the electrocatalyst for the positive electrode of the adjacent cell is coated on the opposite face. In this case, the total cell voltage is the sum of the individual unit cell voltages. Thus, a series-connected stack of such cells forms a module that operates at a higher voltage and lower current than a can-type (monopolar) design. To meet the requirements of large electrolysis equipment, these modules are connected in parallel to increase the current.
Claims
1. A separator (1) for water electrolysis, the separator (1) comprising on at least one side thereof: -Surface area S max , - Surface area S of the surface for contacting the electrode C ,and - a channel (10) having a cross section Φ for venting gas bubbles C , Features: -S C / S max ratio is 0.025 to 0.50, and - The cross section Φ C Large enough to expel bubbles with a diameter of 5 to 50 μm.
2. A separator according to claim 1, wherein the separator (1) comprises a porous layer (200) provided on a porous support (100), and wherein the channels (10) are provided in the porous layer.
3. An isolation element according to claim 1 or 2, wherein the isolation element (1) comprises a first (250) and a second (250') porous layer provided on one side and the other side of the porous support (100), respectively, wherein the channel (10) is provided in the first and / or the second porous layer.
4. The separator of claim 3, wherein the first and the second porous layers are identical. 5 . The separator according to claim 1 , wherein a thickness t2 of the separator is 50 to 750 μm. 6 . The separator according to claim 2 , wherein a thickness t1 of the porous support is 20 to 350 μm.
7. A separator according to any one of the preceding claims having a relative humidity of 2 to 5.8 L / min.cm measured at 5 bar. 2 gas permeability.
8. A separator according to any one of the preceding claims, having a relative humidity of less than 0.1 ohm.cm in a 30 wt% KOH aqueous solution at 80°C. 2 of ionic resistance.
9. A separator according to any preceding claim, wherein the porous layer comprises a polymer and inorganic particles.
10. The separator according to claim 9, wherein the polymer is at least one selected from the group consisting of polysulfone, polyethersulfone, polyphenylene sulfide, polyetheretherketone and polyphenylsulfone.
11. The separator according to claim 9 or 10, wherein the inorganic particles are selected from zirconium oxide, zirconium hydroxide, magnesium oxide, magnesium hydroxide, titanium oxide, titanium hydroxide and barium sulfate.
12. A method of manufacturing a spacer as defined in any one of the preceding claims, the method comprising the steps of: - applying a coating solution onto one side of the porous support (100); - subjecting the applied coating solution to a phase inversion, thereby forming a separator (1), the separator (1) comprising a porous layer (200) on the support; and - During the phase inversion step, channels (10) are provided into the porous layer (200).
13. A method according to claim 12, wherein the channels are provided in the porous layer during the phase inversion step by knurling, embossing or rotogravure printing.
14. A zero-gap electrolysis cell for water electrolysis comprising a separator as defined in any one of claims 1 to 10.
15. Use of a separator as defined in any one of claims 1 to 10 for the production of green hydrogen, green ammonia and green steel.
Citation Information
Patent Citations
Device to arrange and retain long objects in a pallet-like and storable shape
EP0357544A2
Web-reinforced separator and continuous method for producing same
EP1776490A2
Diaphragm for alkaline water electrolysis, method for producing same, and alkaline water electrolysis apparatus
EP3085815A1
Diaphragm for alkaline water electrolysis, alkaline water electrolysis apparatus, method for producing hydrogen, and method for producing diaphragm for alkaline water electrolysis
EP3272908A1
Diaphragm for alkaline water electrolysis, and method for manufacturing same
EP3312306A1